Covid-19 Pandemic: The Study for Reserve Requirement of Indonesia - Dewi Mahrani Rangkuty; Hidayati Purnama Lubis (STIE Jambatan Bulan, 2021)
The Covid-19 pandemic has had an impact on the Indonesian economy. The purpose of this study was to analyze the causality and balanced relationship in the long term between RR, IR and INF variables during the Covid-19 pandemic. With the Granger Causality and Johansen Cointegration test methods, the results showed that there is a long-term balance between RR, IR and INF. RR and IR are one-way causality relationships, IR and INF are one-way causality relationships. There is no causality relationship between IR and RR and vice versa during the Covid-19 pandemic. The RR policy affects the determination of IR and IR affecting Indonesia's INF during the Covid-19 pandemic. To reduce the inflation rate during the pandemic, Bank Indonesia needs to implement RR policy through the determination of interest rates.